Parent-Child Attachment and Social Adaptation Behavior in Chinese College Students: The Mediating Role of School Bonding - Yin, Haowen; Qian, Suning; Huang, Fengqiu; Zeng, Huibin; Zhang, Casper J. P.; Ming, Wai-Kit (Frontiers in Psychology, 2021)
Family and school are two main places for adolescents to flourish socialization, which can be contributed by good parent-child attachment and school bonding. Earlier studies suggested that parent-child attachment played an important role in promoting the formation of high-level school bonding, which is also likely to influence social adaptation formation. This study aimed to explore the relationship between parent-child attachment and social adaptation, and the mediating role of school bonding. Using stratified cluster sampling, 1440 college students were first randomly selected from four universities and then stratified by specialty with a balance between genders and grades. Participants voluntarily participated in this study and completed questionnaires including the Parent-Child Attachment Scale, School Bonding Scale and Social Adaptation Scale. Finally, a total of 1,320 college students were included in the analysis (59.5% female; aged 18-24 years, Mage=20.39±1.52 years). Data analysis and structural equation modeling using SPSS 22.0 and AMOS 23.0. The results indicated that the overall level of parent-child attachment in female (M = 75.72, SD = 12.36) was significantly higher than that of male (M = 73.71, SD = 12.68; F = 8.22, p < 0.01). Difference was also found between Sibling status (F =13.90, p < 0.001), and the only-child (M = 76.16, SD = 12.72) scored significantly higher than their counterparts (non-only children, M =73.60, SD = 12.19). Parent-child attachment was positively correlated with social adaptation ( p < 0.01) and school bonding (p < 0.01), while school bonding was also positively correlated with social adaptation score (p < 0.01). School bonding played a partial intermediary role in the relationship between parent-child attachment and social adaptation (β = 0.15). Our research identified a direct influence of parent-child attachment and an indirect influence via school bonding on social adaptation among college students.